Ethics, Medical Research, and Medicine
XV, 195 p.
Keywords: Andrew Thompson, Norman J. Temple We humans are an extraordinary species. One of our finest achievements is the development of morality, of a sense of right and wrong. We articulate and then impose this sensitivity upon ourselves in the form of ethical guidelines, rules, regulations, and laws. We have, regrettably, also developed marvelously clever ways of justifying our behavior whenever it runs afoul of these prescriptions. We have, for example, developed the concept of objectivity to guide scientific pursuits and subsequently established rights which undermine the possibility of ever coming close to attaining the goal of being objective -- rights which entitle participating scientists to gain personal, tangible profits from scientific discoveries. Formerly, we envisaged gods who kept us in place, who reminded us that we were not all-powerful or especially wise. Now we tend to worship our achievements, especially our technological ones, and ourselves. Mary Midgley' aptly names this phenomenon, "humanolatry." We have lost our respect for nature in our enthusiasm for changing it to that which suits our shortsighted ends. We must, as she says, "unlearn" this way of thinking.